2021
DOI: 10.1002/pri.1900
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability and correlates of the 6‐min walk test in people with alcohol use disorders

Abstract: Objectives People with alcohol use disorders (AUD) are at a higher risk for physical co‐morbidities. Consequently, their daily life functioning needs to be reliably assessed and followed‐up. We examined the reliability of the 6‐min walk test (6MWT) in a cohort of inpatients with AUD. Secondary aims were to assess minimal detectable changes (MDC95), practice effects and associations of the 6MWT with demographical and clinical variables. Methods Two 6MWTs were administered within 3 days to 45 (32♂) inpatients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This (mitochondrial dysfunction) could cause changes in the oxidative phosphorylation system, making it more difficult for them to use oxygen during exercise. Table (5): show that height, weight, BMI, waist circumference, and VAI were significantly correlated with the 6MWD.A study conducted by 34 agreed with our study when they found the 6MWD associated significantly (P < 0.05) Another study conducted by 35 agreed with our study when they found The walked distance in the 6MWT was positively associated with height (r = 0.416; p =0.023).…”
Section: Discussionsupporting
confidence: 79%
“…This (mitochondrial dysfunction) could cause changes in the oxidative phosphorylation system, making it more difficult for them to use oxygen during exercise. Table (5): show that height, weight, BMI, waist circumference, and VAI were significantly correlated with the 6MWD.A study conducted by 34 agreed with our study when they found the 6MWD associated significantly (P < 0.05) Another study conducted by 35 agreed with our study when they found The walked distance in the 6MWT was positively associated with height (r = 0.416; p =0.023).…”
Section: Discussionsupporting
confidence: 79%
“…The 143 included papers studied 49 different clinical tests of physical function. 75 studies assessed the 6-minute walk test (6MWT) (14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87). Fifteen studies analysed the incremental shuttle walk test (ISWT) (18, 37, 56, 58, 68, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97).…”
Section: Resultsmentioning
confidence: 99%